2022
DOI: 10.3390/metabo12040315
|View full text |Cite
|
Sign up to set email alerts
|

The MicroRNA miR-277 Controls Physiology and Pathology of the Adult Drosophila Midgut by Regulating the Expression of Fatty Acid β-Oxidation-Related Genes in Intestinal Stem Cells

Abstract: Cell division, growth, and differentiation are energetically costly and dependent processes. In adult stem cell-based epithelia, cellular identity seems to be coupled with a cell’s metabolic profile and vice versa. It is thus tempting to speculate that resident stem cells have a distinct metabolism, different from more committed progenitors and differentiated cells. Although investigated for many stem cell types in vitro, in vivo data of niche-residing stem cell metabolism is scarce. In adult epithelial tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Unfortunately, there are no animal models for the different CRC stages (I, II, III, IV) since there are only animal models for early or late CRC. This situation makes it difficult to investigate the different markers in vivo and across the different stages, despite the existence of some advanced studies about the use of zebrafish xenografts and Drosophila melanogaster [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are no animal models for the different CRC stages (I, II, III, IV) since there are only animal models for early or late CRC. This situation makes it difficult to investigate the different markers in vivo and across the different stages, despite the existence of some advanced studies about the use of zebrafish xenografts and Drosophila melanogaster [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, miR-277 regulates fatty acid β-oxidation (FAO) enzymes in intestinal stem cells. The differentially expressed genes are identified in miR-277 mutants [ 52 ]. Validations suggested disrupting homeostasis and progenitor cell survival with miR-277 mutants [ 52 ].…”
Section: Micrornas In Drosophilamentioning
confidence: 99%
“…The differentially expressed genes are identified in miR-277 mutants [ 52 ]. Validations suggested disrupting homeostasis and progenitor cell survival with miR-277 mutants [ 52 ]. The alteration of fat metabolism by miR-14 suggested that the triacylglycerol and diacylglycerol levels differ in miR-14 mutants [ 53 ].…”
Section: Micrornas In Drosophilamentioning
confidence: 99%
“…Even though Notch-tumours recapitulate important steps of CRC tumorigenesis, N is not frequently mutated in CRC. Therefore, we also investigated an autonomous function for Crol/ZNF267 in a CRISPR-Cas9 based model of sporadic CRC 48 targeting the most frequently mutated genes with a multiplex guideRNA array (Fig. 6K) [48][49][50] .…”
Section: The 20he-crol-wg Mitotic Balance Is Conserved In Intestinal ...mentioning
confidence: 99%
“…Therefore, we also investigated an autonomous function for Crol/ZNF267 in a CRISPR-Cas9 based model of sporadic CRC 48 targeting the most frequently mutated genes with a multiplex guideRNA array (Fig. 6K) [48][49][50] . CRC in ISC has severe and pleiotropic cellular phenotypes and results in early fly demise 48 .…”
Section: The 20he-crol-wg Mitotic Balance Is Conserved In Intestinal ...mentioning
confidence: 99%